RAD18, WRNIP1 and ATMIN promote ATM signalling in response to replication stress - Kanu, Nnennaya (Oncogene, 2015)
The DNA replication machinery invariably encounters obstacles that slow replication fork progression, and threaten to prevent complete replication and faithful segregation of sister chromatids. The resulting replication stress activates ATR, the major kinase involved in resolving impaired DNA replication. In addition, replication stress also activates the related kinase ATM, which is required to prevent mitotic segregation errors. However, the molecular mechanism of ATM activation by replication stress is not defined. Here we show that monoubiquitinated Proliferating Cell Nuclear Antigen (PCNA), a marker of stalled replication forks, interacts with the ATM cofactor ATMIN via WRN interacting protein 1 (WRNIP1). ATMIN, WRNIP1 and RAD18, the E3 ligase responsible for PCNA monoubiquitination, are specifically required for ATM signalling and 53BP1 focus formation induced by replication stress, not ionising radiation. Thus, WRNIP1 connects PCNA monoubiquitination with ATMIN/ATM to activate ATM signalling in response to replication stress and contribute to the maintenance of genomic stability.